A REVIEW UPDATED ON CHEMOTHERAPEUTICS - Chandra, Akanksha; Soni, Rajesh Kr; Sharma, Upendra; Jain, Sanjay Kr.; Yadav, Prayag (Journal of Drug Delivery and Therapeutics, 2013)
Antineoplastic therapy aims at completely eliminating all neoplastic cells, by either surgical, radio therapeutic or pharmacological (administration of drugs) intervention. If this is not possible or feasible, the aim of therapy becomes palliative, that is, its purpose is to reduce the number of neoplastic cells, to improve the symptoms and, if possible, to prolong survival while maintaining an adequate quality of life. Neoplastic cells constitute a heterogeneous cellular population, with biochemical, morphological and immunological differences. Consequently, they evidence a widely varying sensitivity to antineoplastic drugs. Furthermore, not all the cells present in a given tumor are in the same phase in the cell cycle (generally, in the proliferative or in the rest phase). When a neoplasm is diagnosed, most of its cells have usually attained a phase of decelerated growth, because of vascularisation problems, of nutrient competitively problems, of lack of physical space, or of problems of other types. Many of the chemotherapeutic drugs are most effective on cells that are in their division process, and this means that, in principle, a large proportion of the neoplastic cells will be resistant to the effects of a given drug. The small-molecule drugs are the ones whose molecular weight is less than 1000 Daltons. The fastest growing cells in the body are present in skin, hair follicles and lining of the gastrointestinal tract and hence they are affected the most during chemotherapy. In this present review summarized knowledge of chemotherapy by different way.